Evaluation of Consumers Motivations of Sportswear Teams in the City of Bogota - Zambrano, Diego Sánchez; Mayorga, Oscar Torres; Ramirez, Alejandra Ruiz; Bustamante, Fernando Prieto (European Journal of Sustainable Development, 2017)
The companies of sports clothes (multinationals), specially those who support football teams, make constant changes in their collections, adding new products. For that reason, it is important to know how consumers assimilate these changes in different periods. The last trends, show a increase in the interest of people to acquire new sports articles; for that reason, this research is seeking to identify the motivations of consumers to buy and wish sportswear, evaluates the environmental awareness of the consumer in their decision to purchase those products affected by the changes generated by the planned obsolescence and to determine the correlation between the attributes of the product and the decisions of purchase. In order to obtain this information, 400 surveys were taken. To analyze information, descriptive statistics was used. The instrument was a survey with question a Likert scale, of agreement to the stages of the process of decision of purchase of a consumer. The results of this research shows that the relation between the attributes of the product with regard to the decision of purchase is weak. In fact, data collected reveals how the new styles generate a desire of position and intention of purchase of the new products. Keywords: Motivation, attributes, consumer behavior, sportswear, environmental awareness